Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Splicing mutations in glycogen-storage disease type II: evaluation of the full spectrum of mutations and their relation to patients' phenotypes. - Zampieri, Stefania; Buratti, Emanuele; Dominissini, Silvia; Montalvo, Anna Lisa; Pittis, Maria Gabriela; Bembi, Bruno; Dardis, Andrea (Eur J Hum Genet, 2011)
Glycogen-storage disease type II is an autosomal recessive-inherited disorder due to the deficiency of acid α-glucosidase. A large number of mutations in the acid α-glucosidase gene have been described to date. Among them, ~15% are variations that may affect mRNA splicing process. In this study, we have for the first time comprehensively reviewed the available information on splicing mutations of the acid α-glucosidase gene and we have evaluated their possible impact on the splicing process using different in silico approaches. Out of the 39 different GAA-sequence variations described, an in silico analysis using seven different programs showed that 97% of them are predicted to have an impact on the splicing process. Moreover, this analysis showed a quite good correlation between the impact of the mutation on the splicing process and the clinical phenotype. In addition, we have performed the functional characterization of three novel sequence variants found in Italian patients and still uncharacterized. Using a minigene system, we have confirmed their pathogenic nature. In conclusion, this study has shown that in silico analysis represents a useful tool to select mutations that affect the splicing process of the acid α-glucosidase gene and provides an updated picture of all this kind of mutations reported till now.
Keywords: alpha-Glucosidases; Cell Line; Computational Biology; DNA Mutational Analysis; Exons; Glycogen Storage Disease Type II; Humans; Introns; Mutagenesis, Site-Directed; Mutation; Phenotype; RNA Splicing